The construction of a family farm in the context of the construction of an agricultural holding as provided for in the civil code and in the Act on shaping the agricultural system - Gała, Paweł; Łobos-Kotowska, Dorota; Stańko, Marek (Przegląd Prawa Rolnego, 2021)
The aim of the article is to determine the legal, constitutional and economic assumptions of the legal construction of a family farm in the context of the construction of an agricultural holding in the Civil Code and in the Act of 11 April 2003 on shaping the agricultural system. It has been shown that the provision of Article 23 of the Constitution constitutes only a system declaration, a kind of ideological manifesto. In order for it to be recognised as a directional norm, it should be filled with the relevant content. A definition of a family farm as formulated in the Act on shaping the agricultural system is not sufficient in this respect. It is necessary to formulate a modern construction of such a holding which will meet the requirements of today. However, the direction of these changes should be carefully planned taking into account the agricultural policy of the state.